Application of biomass pyrolytic polygeneration by a moving bed: Characteristics of products and energy efficiency analysis. (April 2018) - Zhang, Xiong; Che, Qingfeng; Cui, Xiang; Wei, Zhiyu; Zhang, Xiaoyan; Chen, Yingquan; Wang, Xianhua; Chen, Hanping
Graphical abstract: Highlights: Moving bed pyrolysis furnace can continuously deal with 7E+03 kg/h of biomass. Torrefaction pretreatment improves the quality of tri-state products. LHV of bio-gas and biochar are respectively 12.5 MJ/m 3 and 30.5 MJ/kg. Total energy efficiency of this pyrolytic polygeneration system reach 57.5%. Abstract: In order to overcome the shortcoming of batch production in the retort and improve the quality of three-state products, a moving bed as pyrolysis furnace and torrefaction pretreatment were both used in a demonstration of biomass pyrolytic polygeneration. The bench and demonstration scale experiments were both investigated in this work. The results show that when the pyrolysis temperature between 550 °C and 750 °C, it can not only maintain the relative stability of the tri-state products yield, but also guarantee the quality. When the demonstration ran at this temperature, it can continuously deal with biomass for about 7E+03 kg/h, and reach 5.42E+07 kg/yr, which can be converted into 1.12E+07 Nm 3 of bio-gas, 3.78E+06 kg of tar, 7.63E+06 kg of vinegar and 1.14E+07 kg of biochar. The lower heating value of bio-gas and biochar were respectively 12.5 MJ/m 3 and 30.5 MJ/kg, which showed the great potential as gas and solid fuel.